Genome Expansion by tRNA +1 Frameshifting at Quadruplet Codons. Issue 8 (30th April 2022) - Gamper, Howard; Masuda, Isao; Hou, Ya-Ming
Graphical abstract: Highlights: Quadruplet decoding requires a +1-frameshifting event of the quadruplet-reading tRNA. No +1 frameshifting occurs in the ribosomal A site. The ribosome permits +1 frameshifting during translocation and P-site occupancy. Abstract: Inducing tRNA +1 frameshifting to read a quadruplet codon has the potential to incorporate a non-canonical amino acid (ncAA) into the polypeptide chain. While this strategy is attractive for genome expansion in biotechnology and bioengineering endeavors, improving the yield is hampered by a lack of understanding of where the shift can occur in an elongation cycle of protein synthesis. Lacking a clear answer to this question, current efforts have focused on designing +1-frameshifting tRNAs with an extra nucleotide inserted to the anticodon loop for pairing with a quadruplet codon in the aminoacyl-tRNA binding (A) site of the ribosome. However, the designed and evolved +1-frameshifting tRNAs vary broadly in achieving successful genome expansion. Here we summarize recent work on +1-frameshifting tRNAs. We suggest that, rather than engineering the quadruplet anticodon-codon pairing scheme at the ribosome A site, efforts should be made to engineer the pairing scheme at steps after the A site, including the step of the subsequent translocation and the step that stabilizes the pairing scheme in the +1-frame in the peptidyl-tRNA binding (P) site.